Design and Integration of a Hybrid Electric Fan Propulsion System - Mastropierro, Francesco (Cranfield University, 2018)
Poster presented at the Cranfield Doctoral Network Annual Event, September 2018.Design and Integration of an Electric Fan Propulsion System for Hybrid Aircraft Electrification is one of the most promising trend for sustaining future aviation beyond the limits of current propulsion technologies. Advantages include lower emissions, higher efficiency components, better energy management and synergies with alternative technologies. Current limits are in higher costs, inferior power density and shorter ranges. Hybrid electric propulsion looks for synergies between current state-of-the-art engines and novel electric motors/batteries, the latter considered as black boxes.The research project aims to investigate quantitatively the unexplored design space for an electric fan propulsion system fitted on a specifically-designed nacelle for regional aircraft. The study entails with the assessments of the overall arrangement and geometry design, evaluating effects of internal pressure losses and cooling air requirements. A viable solution for the organization of the internal volume is the installation of a variable area nozzle. Its adoption would optimise fan performance along a defined mission, allowing a consistent reduction in power and size of electrical components, estimated up to 15%.Additional objectives are the assessment of critical integration aspects of the hybrid technology, such as trade-offs between size and weight of units, degree of hybridization, strategies for efficient energy usage. A techno-economic assessment would top the project, defining viability and economic feasibility of the technology. A realistic evaluation of the uncertainties associated will be included as it is essential to provide solid background to any result.The research uses a combination of dedicated performance software and mainly relies on CFD calculations for the investigation of the internal flows.The project is relevant in the context of evolving aerospace industry, as major companies are consistently investing in electric aviation. It provides contribution to existing knowledge and foundation for future research in the field, both at academic and industrial level.
Keywords: hybrid propulsion'; 'electric fan'; 'nacelle'; 'CranfieldDN2018'; 'Aerospace Engineering'